From Smart System to Smart Governance: Artificial Intelligence for Sustainability - Angreni, Dyah Kuntorini Dwi; Hidayah, Ahmad; Kurniawati, Kamila Dwi (Jurnal Ilmiah Administrasi Publik, 2026)
Artificial Intelligence (AI)  is a transformative technology, that is reshaping the nature of governance systems, creating an unprecedented playing field for sustainable, efficient, and citizen-centric initiatives. It seems there are many challenges when it comes to the use of AI for governance purposes, with both theoretical and ethical gaps in the implementation process. This article discusses the function of AI in the field of sustainable governance and examines global publication trends, thematic interests, and collaborative patterns from 2000 to 2019. In this study, based on a sample of 1044 Scopus-indexed papers, a bibliometrics- and content analysis-based approach is used to identify the major themes, emerging topics, and geographic considerations of the merger of AI and sustainability. The Results indicate that while AI has been studied extensively in various domains (e.g. smart cities, e-governance, environmental management), ethical governance mechanisms, just policy implementation, and broader social implications of AI adoption have received insufficient attention. Filling these gaps, this study contributes to theory development in governance research and is relevant for policymakers to make the deployment of inclusive and ethical AI a reality. This analysis also underscores the importance of concerted interdisciplinary research efforts to strengthen the resilience, trust, and transparency of governance. One clear area in which the research described in this paper does not cover the broad impact of AI technology on sustainability is in developing countries